Analisis Pengaruh Platform E-Commerce dan Media Sosial Terhadap Peningkatan Penjualan UMKM Martabak Manis Tiga Saudara - Lindasari, Rianita Nurani; Isyanto, Puji; Sumarni, Neni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
MSMEs in the culinary sector play an important role in the local economy, but face major challenges in terms of marketing and competition in the digital era. “This study” aims to analyze the influence of e-commerce platforms and social media on increasing sales at the Martabak Manis Tiga Saudara MSME. Using a quantitative approach and survey method on 90 respondents, the data was analyzed using the Structural Equation Modeling (SEM) model using SmartPLS 4. The results of the study indicate that both e-commerce platforms and social media have a significant effect on increasing sales, with social media showing a more dominant influence. In addition, social media also mediates “the influence of e-commerce” on increasing sales significantly. The conclusion of this study is the importance of integrating digital marketing strategies in MSME operations to drive sales growth. The implications of these findings provide recommendations for MSME actors to improve digital capabilities and suggest that further researchers add other relevant variables to expand the scope of future studies.